The Effectiveness of Brainstorming in Teaching Writing - Sutisna, Yayan; Rofi’i, Agus; Kustini, Titin (Papanda Publisher, 2022)
In this research problem, it was found that there were several problems faced by students in writing, such as grammar, spelling, punctuation, and vocabulary choice. Likewise when researchers face problems in teaching programs students are still confused in learning to write, both in expressing ideas or in the correct composition of writing. Brainstorming is a technique that provides a free environment to present individual ideas, without attracting criticism. Each idea generated is recorded and considered as a solution to a problem. the function of the brainstorming technique is one of the techniques that serve to improve writing skills in narrative texts for class XI IPS students at Madrasah Aliyah PUI Maja in 2021/2022. This study aims to determine the effect of using brainstorming in the writing learning process. This research method is a quantitative quasi-experimental, the population in this study is the eleventh social science class, and the data collection technique uses purposive sampling with a total sample of 29 experimental classes and 29 control classes with a total of 58 sample data. The study used normality tests, homogeneity tests, and hypothesis testing. Based on the results of the study, it can be concluded that the experimental class in the std table. deviation can be seen in the difference between the experimental class and the control class 2.117 < 2.525. it means that the experimental class is smaller than the control class, in this case, the brainstorming technique in learning to write in the experimental class there is no significant change compared to the control class in learning to write brainstorming at Madrasah Aliyah PUI Maja.